Impact of global climate change on glaciers and permafrost on South America, with emphasis in Patagonia, Tierra del Fuego and the Antarctic Peninsula - Rabassa, Jorge Oscar
Some of the most important consequences of global climate change (GCC) are rising mean annual or seasonal temperature, rising or diminishing precipitation at the regional level, rising global sea level, and increasing frequency of extreme meteorological events. The impact of these changes has been observed in the glaciers and permafrost areas of South America, particularly the Andean ranges, Patagonia, Tierra del Fuego, and the Antarctic Peninsula at least since 1978 and, particularly in the last decade of the twentieth century. The most noticeable impacts are the fast glacier margin recession, thinning of the ice cover, elevation of the regional snowline, and the reduction of Andean areas under permafrost conditions, as recent scientific research has demonstrated. Small mountain glaciers and ice caps are vanishing all over the Andean ranges, from Venezuela to Tierra del Fuego. At the present rate of ice recession, most, if not all of the cirque glaciers in Patagonia and Tierra del Fuego will disappear during the next two decades, and both valley glaciers and the Patagonian ice sheets will be severely reduced as well. Ice barrier collapse in the Antarctic Peninsula will provide a larger supply of large icebergs which will jeopardize navigation routes, increasing sailing risks in the southern seas, with at least two iceberg-cruiser impacts in the 2007–2008 austral summer. As a consequence of snowline rising and glacier vanishing, damage on environmental, hydrological, geomorphological, heritage, and tourism resources is expected to affect these regions and those communities active in them. Fil: Rabassa, Jorge Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina